1995
DOI: 10.1177/002234099504900402
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Religious Faith and Practice on Patients Suffering from a Major Affective Disorder: A Cost Analysis

Abstract: Presents empirical data showing the relationship between religious beliefs and practices and lengths of stay in the hospital for patients suffering from one form of mental illness. Includes a spiritual injury scale which measures guilt, anger or resentment, sadness/grief, lack of meaning, feeling God/life has treated one unfairly, religious doubt, and fear of death. Shows in statistical form the relationship between these spiritual injuries and length of stay in the hospital. Indicates that spiritual injury is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 0 publications
2
9
0
Order By: Relevance
“…The same relationship between worship and Depression is -3.29 with a p value < 0.001. This finding is consistent with an earlier study on bipolar Disorder that is cited above (Berg, 1995).…”
Section: Resultssupporting
confidence: 94%
“…The same relationship between worship and Depression is -3.29 with a p value < 0.001. This finding is consistent with an earlier study on bipolar Disorder that is cited above (Berg, 1995).…”
Section: Resultssupporting
confidence: 94%
“…In a two-year follow-up of this sample, Pargament and colleagues reported that religious struggle was a significant predictor of increased risk for mortality, even after controlling for demographic, physical health, and mental health variables [12]. These and other studies [13][14][15][16] suggest that some types of religious struggle may contribute to poor physical or mental health outcomes for clinical samples. Evidence of the adverse effects of religious struggle in community samples has also been reported [17][18][19].…”
Section: Introductionmentioning
confidence: 54%
“…Individuals who struggle spiritually, questioning God's presence and sovereignty, report more fear, disillusionment, and distrust of the transcendent (Exline, Yali, & Lobel, 1999). Spiritual struggle has also been linked to psychological outcomes such as anxiety, depression, negative mood, panic disorder, and increased suicide rates , 2000Pargament, Koenig, Tarakeshwar, & Hahn, 2001), and to physical outcomes such as longer hospital stays (Berg, Fonss, Reed, & VandeCree, 1995) and increased mortality following medical illness (Pargament et al, 2001).…”
Section: Spiritual Strugglementioning
confidence: 99%